Tick-borne Diseases in Sheep and Goats in Pakistan: A Systematic Review and Meta-analysis - Mushtaq, Aqsa; Shoukat, Tehniat; Mumtaz, Tanzila; Qasim, Muhammad; Ajmal, Kiran; Fatima, Nayab; Ahmed, Haroon (Springer Int Publ Ag, 2021)
Background Ticks are blood-sucking ectoparasites and transmit various types of protozoal, bacterial, and viral diseases in a wild as well as domestic animals and humans globally. Only a few published reports are avaliable on the prevalence of tick-borne diseases in sheep and goats in Pakistan. Aim and objective The aim of this systematic review and meta-analysis was to evaluate the prevalence (2000-2020) of tick-borne disease (theileriosis, babesiosis, Crimean-Congo hemorrhagic fever infection, and anaplasmosis) in sheep and goats in Pakistan. Methods A systematic review of articles published in English language (since 2000-2020) was conducted using PubMed and Google Scholar. Diagnostic methods used in the original reference articles were PCR, PCR-RLB, microscopy, and ELISA. Results The overall prevalence of theileriosis, babesiosis, anaplasmosis, and Crimean-Congo hemorrhagic fever (CCHF) infections was 15.40%, 21.18%, 26.78%, and 11.62%, respectively. The prevalence of anaplasmosis was 22.06% (90/408) in sheep, 21.11% (76/360) in goats, and 40% (120/300) in both sheep and goats with substantial differences (P < 0.001). The prevalence of babesiosis among sheep was 29.88% (104/348) with highly significant differences (P < 0.001), in goats was 29.88% (25/60) with slightly significant differences (P < 0.031%), and in both sheep and goats were 7% (21/300) with highly significant differences (P < 0.001) according to subgroup analysis. The percentage of prevalence of theileriosis was 17.70% (207/1169) in sheep with highly substantial differences (P < 0.001), 4.51% (31/687) in goats with significant differences (P < 0.133), and 25% (125/500) in both sheep and goats with a significant difference among them (P < 0.001). The prevalence of CCHF among sheep was 18.63% (149/800) and 4.63% (37/800) in goats, respectively. The widely used detection method was microscopy (45.56%) followed by ELISA (38.38%), PCR (12.56%), and PCR-RLB (3.48%) test, respectively. This is a comprehensive report on the status of tick-borne disease in sheep and goats in Pakistan. Conclusion Based on our results, among tick-borne diseases anaplasmosis had the highest prevalence rate in sheep and goats. Due to its high prevalence, control measures should be taken to diagnose and prevent it.
Keywords: Tick-borne diseases; Sheep; Goat; Meta-analysis; Pakistan